Effect of Induced Moulting in Male and Female Line Broiler Breeder Hens by Zinc Oxide and Feed Withdrawal Methods on Post Molt Performance Parameters - Reddy, Venkata; Malathi, V.K.; Reddy, B.S. Venkatarami (International Journal of Poultry Science, 2008)
A study was conducted to evaluate zinc oxide and total feed withdrawal techniques to induce moulting in two heavy breeds viz., Red Cornish (male line) and White Plymouth Roock (female line) and their effects on body weight, reproductive organs, egg production, feed consumption, feed efficiency, egg characteristics, fertility, hatchability and mortality. 180 male line Cornish, 180 female line white Plymouth Rock above 60 weeks of age were selected and distributed to 60 pens with 6 birds in each pen. Three experimental treatments consisting of control, zinc oxide (25,000 pm) and feed withdrawal till the end of production, were allotted to 10 pens for each treatment in each row separately for both the breeds. Changes in reproductive organs were studied on ‘0’ day of the trial, at 0 and at 50% production. The Cornish layers lost an average about 16% due to zinc oxide and about 14.9% due to feed withdrawals and the Rock layers lost about 21.74 and 16.18%, respectively. In both the breeds the reproductive organs loss was more in feed withdrawal groups when compared to zinc oxide groups. Hen day egg production in Cornish in the treated groups did not differ significantly from the control, whereas, in Rock, a significant increase in hen day egg production was noticed in both the treatments. Rock layers consumed slightly higher quantity of feed compared to Cornish layers throughout the four 28 day periods. In both breeds the eggs from control birds had significantly low Haugh unit score when compared to those from moulted groups. There was no significant difference in fertility and hatchability due to different methods of moulting in both the breeds. However, Rock hens showed slightly higher fertility and hatchability than the Cornish hens. Mortality rate did not vary between the breeds. In conclusion, the feed withdrawal method appears to be better in inducing moult in broiler breeder hens than the zinc oxide method.